Whitening toothpastes effect on enamel surface morphology, chemical profile and color : an In Vitro study = Efecto de las pastas dentales blanqueadoras sobre la morfología, el perfil químico y el color de la superficie del esmalte : un estudio In Vitro - Mohsen, Rania Osama M.
To assess the effect of different whitening toothpastes on enamel surface morphology, chemical profile and their whitening efficiency. Sixty teeth were divided into 5 groups (12 teeth/group); Gp I: brushed with no toothpaste. Gp II: brushed with Pearl-based toothpaste. Gp III: brushed with Charcoal-based toothpaste. Gp IV: brushed with Alumina-based toothpaste. Gp V: brushed with salt and lemon-based toothpaste. Each tooth was brushed with a bean sized toothpaste wetted with distilled water twice daily by using standard electronic toothbrush for four weeks. Enamel surface morphology, chemical profile and color of each tooth were investigated. Chemical profile results and color measurements were analyzed statistically. Gp I revealed normal enamel surface morphology and chemical profile. Gp II and Gp III demonstrated surface morphology close to Gp I with insignificant reduction in mineral content. Gp IV showed obvious shallowing of perikymata ridges, exposure of fish-scale appearance, with pits and depressions, alongside to the significant reduction in mineral content. Gp V presented the most enamel surface alteration with widening of prism sheath and depressions all over the surface, besides the highest significant reduction in mineral content. Gp V, followed by Gp IV, demonstrated the highest color and whiteness changes, followed by Gp III, then Gp II, while the lowest value was in Gp I. Salt & lemon-based toothpaste, followed by Alumina-based, exerted the most considerable changes in the morphology and chemical profile of the enamel surface, beside to the higher whitening effects on teeth than the others.